Evaluation of epididymis storage temperature and cryopreservation conditions for improved mitochondrial membrane potential, membrane integrity, sperm motility and in vitro fertilization in bovine epididymal sperm. (7th December 2016) - Nichi, M; Rijsselaere, T; Losano, JDA; Angrimani, DSR; Kawai, GKV; Goovaerts, IGF; Van Soom, A; Barnabe, VH; De Clercq, JBP; Bols, PEJ
Contents: The maintaining of the epididymis at lower temperatures during storage and transport improves sperm quality. Our study aimed to test whether epididymis storage temperature (post‐mortem) and sperm cryopreservation affect sperm kinetics, membrane integrity, mitochondrial potential and fertility capacity. Thirty‐six epididymides were collected from 18 bulls after slaughter and divided into two groups: at 4 or 34°C for 2–3 hr. The sperm was collected from the epididymis cauda. The evaluation consisted of computer‐assisted sperm analysis (CASA), SYBR14/PI/JC1 to evaluate membrane integrity, mitochondrial membrane potential (MMP) and measurement of lipid peroxidation (TBARS). The sperm was then frozen using an automatic device. After thawing, sperm samples were evaluated by the same variables and further in vitro fertilization rates. Cryopreservation negatively affected sperm motility in samples stored at 4 and 34°C. Nevertheless, the 4°C samples yielded higher rates of blastocyst formation. Pre‐freeze sperm motility, progressive motility and velocity were higher in sperm from epididymis stored at 4°C while post‐thaw sperm motility, progressive motility and velocity remained the same among samples from epididymis stored at 4 or 34°C. However, with regard to the kinetic patterns, samples collected from epididymis stored at 34°C had lower values when compared to those stored at 4°C prior the cryopreservation process. Our results indicate that epididymis handling conditions after cryopreservation may affect sperm quality after thawing, especially due to compromised MMP in sperm collected from epididymis stored at higher temperatures.